3rd annual rare plant symposium: presentation - Colorado Natural Heritage Program, author (Colorado State University. Libraries, 2006)
A review of southeast Colorado G2 plant species.
Symposium held on September 8, 2006 at University of Colorado, Colorado Springs in Colorado Springs Colorado.
Presented by the Colorado Rare Plant Technical Committee.
Keywords: Rare plants -- Colorado -- Identification; Endemic plants -- Colorado -- Identification; Endangered plants -- Colorado -- Identification